Do ruido à interdependencia: a trajetória possível do diálogo competitivo para contratações públicas de inovação - Santos, Alessandra Cristina Fagundes dos (Universidade do Vale do Rio dos Sinos, 2024)
The research has as its object the interaction between the State and the market, within the scope of the so-called competitive dialogue, a new modality for public procurement and the potential as an instrument to encourage innovation, on the demand side. The research problem started from the risks and uncertainties of the effectiveness of the bidding, since the backbone of the new bidding modality is in the dialogue between public and private organizations. From this, it was asked how to mitigate the communication noise in public-private interaction, in the context of competitive dialogue, for the effectiveness of the instrument in public policy to encourage innovation, on the demand side? As a hypothesis, it was defined that the mechanism of communicational interdependence is the key to the success of public contracting of innovation via competitive dialogue as a way to overcome the challenge, enabling not only the enhancement of the use of the modality, but also the scope of the effectiveness of public procurement. As a general objective, it was intended to contribute to the consolidation of competitive dialogue as a public policy mechanism aimed at stimulating innovation from the perspective of demand. In addition, it was sought that this instrument, of dialogic regulation and collaborative participation, contributes to the adaptation of the organizational culture in favor of public-private coevolution, through new communicative processes of construction of meaning. As specific objectives of the research, it contextualized the path taken by the contemporary State until the reform of the New Law of Bids and Administrative Contracts (NLLCA), dealing with the peculiarities of competitive dialogue for public procurement; pointed out the challenges of instrumentalizing competitive dialogue and analyzing the differences in the organizational culture of the public and the private and possible factors of noise and disturbances during public-private interaction in the bidding environment; presented the theoretical mechanism of communicational interdependence in an environment of trust as a key piece for collaboration between public and private economic agents; and, it delivered a framework as an artifact to support agents in the procedure of competitive dialogue. The relevance of the research consisted in the exploration of competitive dialogue as a mechanism that induces the effectiveness of innovative public contracts; the development of new innovative markets; and the effectiveness of the demand-based innovation policy. The analytical approaches conducted to confirm the hypothesis used the theory of social systems as a theoretical framework, from the perspective of Niklas Luhmann. The methodology to produce epistemological knowledge used to confirm the hypothesis was the hypothetical-deductive approach, where it was sought, from the research problem and formulated hypothesis, to test whether the predictions derived from the initial hypothesis are supported or refuted by the results obtained. For the artifact, the Design Science Research (DSR) methodology was used. As a research technique, qualitative and exploratory approaches were used from data collection. The conclusion pointed out that competitive dialogue not only enables innovative solutions, but also promotes the co-evolution of organizations, where communicative noises become communicative stimuli, ensuring that both remain autonomous and operational in a collaborative environment.
Keywords: Diálogo competitivo; Contratações públicas; Interdependência comunicacional; Colaboração; Cultura organizacional; Competitive dialogue; Public procurement; Communicational interdependence; Collaboration; Organizational culture; ACCNPQ::Ciências Sociais Aplicadas::Direito